2009
DOI: 10.1021/jz900008y
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photoresponse of Inkjet-Printed ZnO Thin Films Capped with CdS Nanoparticles

Abstract: Composite semiconductors provide routes for realizing high-performance electronic devices, but for many applications of such devices, low-cost manufacturing techniques are desirable. We have engineered a 3 orders of magnitude enhancement of the ultraviolet photoresponse of ZnO thin films, fabricated "in situ" by drop-on-demand inkjet printing, and then capped with CdS nanoparticles by dip coating. As a consequence, the decay time of the photoresponse is reduced to about 4 ms. Thus, capping with CdS not only su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Of these, Cu 2 S is considered to be promising materials as absorbers of visible light, due to its band gap energy 1.2-2.4eV [1][2]. Besides, ZnO has been a heated object in recent years, as a potential ultraviolet, blue and other visible optical device materials owing to its wide and direct band gap 3.1-3.3eV [3][4][5][6]. Additionally, polycrystalline ZnO has been found for numerous interesting applications, such as piezoelectric transducers transparent conducting lms [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, Cu 2 S is considered to be promising materials as absorbers of visible light, due to its band gap energy 1.2-2.4eV [1][2]. Besides, ZnO has been a heated object in recent years, as a potential ultraviolet, blue and other visible optical device materials owing to its wide and direct band gap 3.1-3.3eV [3][4][5][6]. Additionally, polycrystalline ZnO has been found for numerous interesting applications, such as piezoelectric transducers transparent conducting lms [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the fabrication methods used so far involve multistep photolithography and vacuum‐deposition processes which contribute to their high manufacturing costs. In comparison, direct printing of inorganic materials offers the possibilities of depositing thin films using direct additive patterning processes that enable the fabrication of high‐performance and ultra low‐cost electronic components 6–8. Recently, using inkjet printing Lee et al 7, 9, 10 reported amorphous IZO‐FETs with a mobility of 7.4 cm 2 V −1 s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, some intriguing studies reported on enhanced photoresponse of inkjetted ZnO thin films by embedding other NPs to improve interfacial charge transfer. Wu and coworkers [126] demonstrated that the photoconductivity of ZnO NP thin films fabricated by DOD inkjet printing (treated at 400 • C to achieve crystallization) and then capped with CdS NPs, was improved by three orders of magnitude under UV irradiation, with respect to the pure ZnO film (Figure 16a-d). The decay time was also reduced to~4 ms.…”
Section: Zno-based Formulations For Inkjet Printing and Related Devicesmentioning
confidence: 99%